2011
DOI: 10.1017/s000711451100242x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anthocyanins on expression of matrix metalloproteinase-2 in naproxen-induced gastric ulcers

Abstract: Non-steroidal anti-inflammatory drugs cause gastric ulceration through a number of mechanisms including inhibition of PG synthesis, generation of reactive oxygen species (ROS) and induction of apoptosis. Recently, matrix metalloproteinases (MMP) have been suggested to play a crucial role in these mechanisms. The present study investigated the protective effect of anthocyanins isolated from black rice bran (Heugjinjubyeo) against naproxen-induced gastric mucosal injury in rats. The oral administration of anthoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…Some studies have shown that expression of MMP 2 and MMP 9 is highly pronounced in tumor tissues as compared with normal tissue and that polymorphisms rs2285052 of gene MMP 2 and rs3918242 of gene MMP 9 play an important role in the development of gastric ulcers and stomach cancer [27,28]. MMP 9, one of the most important MMPs, is known for degrading the extracellular matrix and basement membrane, thereby contributing to disease progres sion of various cancers by increasing the migration, invasion, metastasis, and angiogenesis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that expression of MMP 2 and MMP 9 is highly pronounced in tumor tissues as compared with normal tissue and that polymorphisms rs2285052 of gene MMP 2 and rs3918242 of gene MMP 9 play an important role in the development of gastric ulcers and stomach cancer [27,28]. MMP 9, one of the most important MMPs, is known for degrading the extracellular matrix and basement membrane, thereby contributing to disease progres sion of various cancers by increasing the migration, invasion, metastasis, and angiogenesis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) levels were measured using a commercial assay kit (Cayman chemical, Ann Arbor, MI, USA) according to the manufacturer’s instructions. Proteins were determined by the method of Bradford (Kim et al ., 2011b). …”
Section: Methodsmentioning
confidence: 99%
“…Although a detailed analysis of the peripheral factors involved in the mucosal protection was above the scope of the present study, we addressed the question of whether allyphenyline is able to counteract oxidative stress, an important factor in the pathomechanism of various experimental ulcers (e.g. NSAID, stress, ethanol) [55][56][57][58], as well as in H. pylori-associated ulcers [59]. It is well-established that excessive production of reactive oxygen species (ROS) and/or their decreased elimination by antioxidant enzymes induce cell and tissue damage by promoting lipid peroxidation and increasing the production of inflammatory mediators and proinflammatory cytokines [60].…”
Section: It Is Well-established That Peptic Ulcers Develop As a Resumentioning
confidence: 99%
“…Reduced mucosal antioxidative capacity and increased level of lipid peroxidation products (e.g. malondialdehyde) correlate well with macroscopic and histological mucosal damage, and agents endowed with antioxidant property are able to prevent ROS-mediated cellular damage [55][56][57][58]61]. Our results show that allyphenyline significantly increased the mucosal content of SOD (which enzyme catalyzes the dismutation of O2˙− into less noxius hydrogen peroxide (H2O2)) and CAT (which accelerates the breakdown of H2O2 to water and oxygen) compared to the ethanol-treated group, suggesting that the gastroprotective action of allyphenyline -at least partly -relies on its ability to enhance the activity of mucosal antioxidant enzymes and reduce the damaging effect of ROS.…”
Section: It Is Well-established That Peptic Ulcers Develop As a Resumentioning
confidence: 99%